Factors Contributing to Unprofessional Behaviour among Nursing Students at the University of Namibia - Ashipala, Daniel Opotamutale; Shaluwawa, Selma Iyaalo (Africa Journal of Nursing and Midwifery, 2021)
Globally, there is a universal expectation that nurses should have a duty to serve others with commitment and dedication. Therefore, it is expected from all professional nurses including nursing students that they behave professionally and ethically in accordance with the ethical codes of practice and conduct. Unprofessional behaviour among student nurses has the potential to negatively affect staff and workplace relationships, and most importantly, compromise patient safety and care. The factors contributing to unprofessional behaviour among nursing students in Namibia have not been extensively researched. This requires institutions of higher learning to establish which factors are likely to promote unprofessional behaviour among student nurses, which could then be used to deal with unprofessional behaviour among these students. The objectives of this study were to explore and understand the factors contributing to unprofessional behaviour among nursing students at the University of Namibia. A qualitative, explorative, descriptive and contextual study was conducted. The accessible population in this study consisted of 17 undergraduate nursing students. Purposive sampling was used and the requisite data collected from the 17 participants using individual semi-structured interviews. The data were analysed by means of qualitative content analysis. Three themes were subsequently identified, namely, unprofessional behaviour in nursing, factors contributing to unprofessional behaviour, and moulding unprofessional behaviour. These findings call for well-articulated plans on the part of the faculty management team to deal with unprofessional behaviour among nursing students. It is recommended that further research be conducted to identify specific curriculum components that may be incorporated to strengthen the teaching of nursing ethics to students.